Juvenile delinquency profiles: associated and contrasting factors in types of crimes committed by adolescents in conflict with the law - Benites Guerrero, Sebastián Darío (2024)
"It has been identified that the most frequent crimes among young people in youth centers in Peru are: aggravated robbery, sex crimes, illicit drug trafficking, and homicide. These types of crime are usually studied from associated factors that are similar, incorporating psychological and sociological variables. However, there are nuances and contrasts in the profiles of young people depending on the type of crime recorded. Therefore, this research proposes a comparative analysis of the four types of crimes mentioned. The objective is to show contrast between the profiles of young people according to associated factors and to indicate if any of these acquire greater explanatory force for one crime or another. For this, the research was carried out using a quantitative methodology, analyzing the data provided by the Population Survey of Juvenile Detention Centers during 2022. Logistic regressions were carried out to show the contrast between the types of crime and the associated factors. The results of the research show contrasting profiles according to some key factors. Some of these findings are: the association of criminal gangs with the crime of homicide, factors linked to the biographical history in the childhood stage with the sex crimes, and the influence of peers and educational dropout in the case of aggravated robbery. In the case of adolescents who committed drug trafficking, an exploration of other types of factors is required; those used did not generate a contrasting profile."